Efficiency of the dose rate calculation by Monte-Carlo method and point kernel method when handling radioactive waste - Rudychev, V.G.; Azarenkov, N.A.; Girka, I.O.; Rudychev, Y.V. (Вопросы атомной науки и техники, 2018)
For the gamma-radiation sources with the volume up to 1 m³ , filled with typical radioactive waste generated at NPPs with WWER-1000 reactors, the results of the dose rate (DR) calculations made by Monte-Carlo (MCNP) and by point kernel method (MicroShield and VOLUME) are compared. It is shown that the difference of the DR calculations made by the above methods does not exceed 10%. The values of DR calculated in MicroShield and VOLUME packages for the shields made of concrete and steel for such sources overestimate the MCNP data by 20…50%. The optimal correction of the buildup factor in the VOLUME package gives an accuracy of 10% in the shield calculations. Для джерел гамма-випромінювань з об'ємом до 1 м³ , заповнених типовими радіоактивними відходами, що утворюються на АЕС з реакторами ВВЕР-1000, проведено порівняння результатів розрахунків потужності доз (ПД) методами Монте-Карло (MCNP) і інтегрування точкових джерел (MicroShield і VOLUME). Показано, що при розрахунках ПД методами Монте-Карло та інтегрування точкових джерел різниця в результатах не перевищує 10%. Результати розрахунків захисних споруд з бетону і сталі для таких джерел у пакетах MicroShield і VOLUME дають завищені значення ПД (20…50%) у порівнянні з даними пакета MCNP. Оптимальне коригування фактора накопичення в пакеті VOLUME дає точність розрахунків захистів приблизно 10%. Для источников гамма-излучений с объемом до 1 м³ , заполненных типичными радиоактивными отходами, образующимися на АЭС с реакторами ВВЭР-1000, проведено сравнение результатов расчетов мощности доз (МД) методами Монте-Карло (MCNP) и интегрирования точечных источников (MicroShield и VOLUME). Показано, что отличие в результатах не превышает 10% при расчетах МД методами МонтеКарло и интегрирования точечных источников. Результаты расчетов защит из бетона и стали для таких источников в пакетах MicroShield и VOLUME дают завышенные значения МД (20…50%) по сравнению с данными пакета MCNP. Оптимальная корректировка фактора накопления в пакете VOLUME дает точность расчетов защит около 10%.